A gut reaction? The role of the microbiome in aggression - Uzan-Yulzari, Atara; Turjeman, Sondra; Moadi, Lelyan; Getselter, Dmitriy; Rautava, Samuli; Isolauri, Erika; Khatib, Soliman; Elliott, Evan; Koren, Omry (Academic Press, 2025)
Recent research has unveiled conflicting evidence regarding the link between aggression and the gut microbiome. Here, we compared behavior profiles of control, germ-free (GF) and antibiotic-treated mice, as well as re-colonized GF mice to understand the impact of gut microbiome on aggression using the resident-intruder paradigm. Our findings revealed a link between gut microbiome depletion and higher aggression, accompanied by notable changes in urine metabolite profiles and brain gene expression. Our study extends beyond classical murine models to humanized mice to reveal the clinical relevance of early-life antibiotic use on aggression. Fecal microbiome transplant from infants exposed to antibiotics in early life (and sampled one month later) into mice led to increased aggression compared to mice receiving transplants from unexposed infants. This study sheds light on the role of the gut microbiome in modulating aggression and highlights its potential avenues of action, offering insights for development of therapeutic strategies for aggression-related disorders.